Volatility Risk and Uncertainty in Financial Markets - Schwartz, Robert A.; Byrne, John Aidan; Colaninno, Antoinette (Zicklin School of Business Financial Markets Series, 2011)
Volatility is very much with us in today's equity markets. Day-to-day price swings are often large and intra-day volatility elevated, especially at market openings and closings. What explains this? What does this say about the quality of our markets? Can short-period volatility be controlled by better market design and a more effective use of electronic technology? Featuring insights from an international array of prominent academics, financial markets experts, policymakers and journalists, the book addresses these and other questions concerning this timely topic. In so doing, we seek deeper knowledge of the dynamic process of price formation, and of the market structure and regulatory environment within which our markets function.   The Zicklin School of Business Financial Markets Series presents the insights emerging from a sequence of conferences hosted by the Zicklin School at Baruch College for industry professionals, regulators, and scholars. Much more than historical documents, the transcripts from the conferences are edited for clarity, perspective and context; material and comments from subsequent interviews with the panelists and speakers are integrated for a complete thematic presentation. Each book is focused on a well delineated topic, but all deliver broader insights into the quality and efficiency of the U.S. equity markets and the dynamic forces changing them.